2006
DOI: 10.1016/j.rmed.2006.01.014
|View full text |Cite
|
Sign up to set email alerts
|

Side effects due to primary antituberculosis drugs during the initial phase of therapy in 1149 hospitalized patients for tuberculosis

Abstract: It must be remembered that severe side effects associated with anti-TB drugs were encountered with different frequencies especially among patients hospitalized for pulmonary tuberculosis, and these patients should be followed up by closer monitoring for side effects related to anti-TB drugs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
97
2
6

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(118 citation statements)
references
References 24 publications
(58 reference statements)
10
97
2
6
Order By: Relevance
“…The present study reaffirmed a significantly higher risk of drug-induced hepatitis among older patients [1,2,4,6,7,13,15] although a few studies showed negative findings [5,11]. The present findings also corroborated a case-control study in Hong Kong that showed only age and hepatitis B infection were significantly related to anti-TB treatment [6], although the risk of drug-induced hepatitis due to chronic hepatitis B may have been over-estimated by assuming negative results for those with unknown HBsAg.…”
Section: Table 1 Continuedsupporting
confidence: 77%
See 1 more Smart Citation
“…The present study reaffirmed a significantly higher risk of drug-induced hepatitis among older patients [1,2,4,6,7,13,15] although a few studies showed negative findings [5,11]. The present findings also corroborated a case-control study in Hong Kong that showed only age and hepatitis B infection were significantly related to anti-TB treatment [6], although the risk of drug-induced hepatitis due to chronic hepatitis B may have been over-estimated by assuming negative results for those with unknown HBsAg.…”
Section: Table 1 Continuedsupporting
confidence: 77%
“…isk factors for hepatitis have been evaluated by a number of observational studies [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15] but few addressed treatment-related factors [12][13][14][15]. While the latter focused on the risk of hepatitis induced by individual drugs, the impact of dosing schedules has not been adequately addressed.…”
mentioning
confidence: 99%
“…Incidence of hepatotoxicity was between 2.4-11.3 % in Turkish population (5,(18)(19)(20)(21). The high variance for hepatotoxicity among studies may be attributed to different patient groups as genetic factors play an important role in the development of hepatotoxicity.…”
Section: Discussionmentioning
confidence: 99%
“…Serious side effects caused by tuberculosis treatment [18] leads to discontinuation of the treatment equally in patient infected with HIV and in patient who were not [19].…”
Section: Barrier In Treatment Completionmentioning
confidence: 99%